2013
DOI: 10.1016/j.brainresbull.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated exposure to MDMA on the function of the 5-HT transporter as assessed by synaptosomal 5-HT uptake

Abstract: Recent studies have demonstrated that a preconditioning regimen (i.e., repeated low doses) of MDMA provides protection against the reductions in tissue concentrations of 5-HT and 5-HT transporter (SERT) density and/or expression produced by a subsequent binge regimen of MDMA. In the present study, the effects of preconditioning and binge treatment regimens of MDMA on SERT function were assessed by synaptosomal 5-HT uptake. Synaptosomal 5-HT uptake was reduced by 72% 7 days following the binge regimen (10 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several factors have received significant attention regarding the mechanisms underlying substituted amphetamine preconditioning. Evidence has been presented for a variety of potentially relevant cellular/biochemical/molecular changes [9,11,19,21,29,36,44,60,61,70]. But until additional research is conducted, it will remain unclear whether these changes work in concert or whether there are multiple pathways leading to the neuroprotective effects of low-dose MDMA or METH administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have received significant attention regarding the mechanisms underlying substituted amphetamine preconditioning. Evidence has been presented for a variety of potentially relevant cellular/biochemical/molecular changes [9,11,19,21,29,36,44,60,61,70]. But until additional research is conducted, it will remain unclear whether these changes work in concert or whether there are multiple pathways leading to the neuroprotective effects of low-dose MDMA or METH administration.…”
Section: Discussionmentioning
confidence: 99%
“…Ecstasy (3,4-methylenedioxymethamphetamine, or MDMA) can cause synaptic 5-HT release, induce heat production and hyperactivity, deplete 5-HT, and damage nerve terminal structures (14). If MDMA was used five times within 24 hours, the concentration of 5-HT would not recover until 110 days later (15). Studies have shown that acute administration of MDMA affects the normal synthesis, operation, and metabolism of 5-HT by changing the expression of 5-HT-related genes (16).…”
Section: Mechanism Of 5-hydroxytryptamine In Drugmentioning
confidence: 99%
“…Most studies on the evaluation of serotonin transport via SLC6A3, SLC6A4/5‐HTT/SERT, SLC18A2 and SLC22A3 by chromatographic techniques have used HPLC–EC, usually with an octadecylsilyl (C 18 ) column (Table ). Serotonin has been determined in brain dialysates, cochlear supernatants, plasma and various tissues by HPLC–EC (Armando et al, ; Callaghan et al, ; Cedeño et al, ; Choi et al, ; Fazzino et al, ; Feng et al, ; Huff et al, ; Kim et al, ; Kish et al, ; Kreiss et al, ; Linder et al, , , ; Nakatani et al, ; Ni et al, ; Ni et al, ; Pazzagli et al, ; Reader et al, ; Ren‐Patterson et al, ; Sánchez et al, ; Taylor et al, ; Tsuruoka et al, ; Vicente‐Torres et al, ; Vogel et al, ; Wei et al, ; Zhang et al, ; Zhou et al, ) and by HPLC–FL (Huang et al, ). Fanzzino et al demonstrated serotonin determination in human monocytes and lymphocytes (Fazzino et al, ).…”
Section: Transport Of Endogenous Compounds As Determined By Chromatogmentioning
confidence: 99%